2011
DOI: 10.1007/8904_2011_68
|View full text |Cite
|
Sign up to set email alerts
|

Identification of 11 Novel Homogentisate 1,2 Dioxygenase Variants in Alkaptonuria Patients and Establishment of a Novel LOVD-Based HGD Mutation Database

Abstract: Enzymatic loss in alkaptonuria (AKU), an autosomal recessive disorder, is caused by mutations in the homogentisate 1,2 dioxygenase (HGD) gene, which decrease or completely inactivate the function of the HGD protein to metabolize homogentisic acid (HGA). AKU shows a very low prevalence (1:100,000-250,000) in most ethnic groups, but there are countries with much higher incidence, such as Slovakia and the Dominican Republic. In this work, we report 11 novel HGD mutations identified during analysis of 36 AKU patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 29 publications
2
36
0
1
Order By: Relevance
“…13 Although a clear founder effect was observed in the Dominican republic, 11 in Slovakia, already 13 different HGD variants affecting function are reported in 121 AKU chromosomes, though most of the patients in this country come from a previously genetically isolated region. [7][8][9][32][33][34][35] The most frequent variant found in Slovakia is p.Gly161Arg, present in 45% of all AKU alleles (HGD mutation database).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…13 Although a clear founder effect was observed in the Dominican republic, 11 in Slovakia, already 13 different HGD variants affecting function are reported in 121 AKU chromosomes, though most of the patients in this country come from a previously genetically isolated region. [7][8][9][32][33][34][35] The most frequent variant found in Slovakia is p.Gly161Arg, present in 45% of all AKU alleles (HGD mutation database).…”
Section: Discussionmentioning
confidence: 99%
“…8 Variants were reported according to the Human Genome Variation Society (HGVS) nomenclature additions 16 and their description is based on coding DNA Reference Sequence NM_000187.3 (genomic reference sequence NG_011957.1). Exons are numbered like in the study by Granadino et al 4 Variants and other patient data were deposited in the HGD gene mutation database (http://hgddatabase.cvtisr.sk/), 8 using a specific family/allele code. Variant nomenclature was verified using MUTALYSER Name Checker (https://www.mutalyzer.nl/).…”
Section: Variant Identificationmentioning
confidence: 99%
See 1 more Smart Citation
“…The downregulated gene with the largest ES (1.2299) was mitochondrial ribosomal protein S11 (MRPS11), which plays a role in protein synthesis within the mitochondrion (Emdadul Haque et al, 2008). The downregulated gene with the lowest P value (0.005673) was homogentisate 1,2-dioxygenase (HGD), which is involved in the catabolism of the amino acids tyrosine and phenylalanine (Zatkova et al, 2012). HGD deficiency is associated with bone deformity in AS (Balaban et al, 2006).…”
Section: Identification Of De Genes In Asmentioning
confidence: 99%
“…At this writing, 174 unique HGD sequence variants found in 398 individuals carrying a total of 751 variants are reported in the database. In particular, the missense mutation c.1078G>C; p.Gly360Arg (henceforth, G360R) in exon 13 has been detected 13 times in patients from Italy, Australia, the UK, France and the USA (Zatkova et al 2012). G360R was originally described by Porfirio et al (2000) who found two independent G360R-bearing AKU chromosomes in two patients from different ends of the Italian peninsula; one patient was a compound heterozygote from Calabria, Southern Italy, whereas the other was the affected son of a consanguineous marriage from South Tyrol, a German-speaking region on the Austrian border.…”
mentioning
confidence: 99%